Photometric Determination of Benzoyl and Salicyloyl Hydrazines with Vanadium(V) - Rambabu, C.; Chandrasekhara Rao, M.; Somasekhara Rao, Kaza (Asian Journal of Chemistry, 2010)
The results of the photometric determination of benzoyl hydrazine (BH) and salicyloyl hydrazine (SH) with vanadium (V) in phosphoric acid medium are reported. Osmium tetroxide is found to catalyse the reaction. All the titrations are carried out in presence of 2–6 ml of orthophophoric acid and 0.5 ml of OsO4 in a total volume of 25 ml, by following the increase in intensity of blue colour of vanadium(IV) at its maximum wavelength.